La inadecuada preparación deportiva y su incidencia en el esguince de tobillo en futbolistas. Federación Deportiva Los Ríos, septiembre 2017 - febrero 2018 - Sellan Fernández, Angela Marina (2018)
The research activity that gave rise to the writing of this final thesis report was to evaluate how sports training affects the appearance of sprained ankle in footballer of the Sports Federation of Los Rios. In the development of the research, empirical and theoretical methods of scientific research were conveniently applied, in the data collection and the corresponding analysis of the results obtained respectively in the different phases where the scientific work was carried out, using the mathematical and statistical methods for process the acquired information and provide it with the expected scientific value. The investigation was justified, the initial diagnosis obtained, which revealed the number of players who suffered ankle sprain in the period studied, also reflecting the shortcomings of the sports training developed, this opinion conditioned the essential basis for the development of a system of actions, aimed at solving the existing scientific problem, which would result in the elevation of the health levels of the athletes under study, the scientific result reached was evaluated by 7 experts, selected according to criteria supported by Font, in the year 2012, the research achieved results that if taken into account by the direction of the sports institution object of studies, can cause positive and significant impacts on the practice of soccer in the territory occupied by the province of Los Rios, by decreasing the number of ankle injuries.